(untitled) (Research, Society and Development, 2022)
The root lesion nematode has caused increasing economic damage to crops on farms in Brazil, especially in the Midwest region. The objective of this work was to know the distribution of the root lesion nematode, Pratylenchus spp., in the State of Mato Grosso, making it possible to know the locations with the highest concentration of this nematode over time. Through data obtained from reports issued in the period from 2006 to 2015, analyzes of abundance, frequency of occurrence, autocorrelation were carried out and maps of the population density of Pratylenchus spp. in the State. Annual data on average temperature, annual rainfall, productivity and planted area in the state in the period were also analyzed. The Pratylenchus genus is present in 85% of the samples, presenting an abundance of 76% of incidence compared to other phytopathogenic genera. The municipalities of Sapezal (12%), Sorriso (9%), Diamantino (8%), Campo Novo do Parecis (8%), Primavera do Leste (6%), Sinop (5%), Nova Mutum (4%) and Querência (4%) were the ones with the highest abundance of Pratylenchus spp., indicating a high level of infestation of the pathogen in the central region of the State of Mato Grosso, with the year 2011 having the highest infestation. It was observed that there was an increase in the planted area, but the productivity remained close to the average of 3.405 Kg ha-1, years with rainfall above 1100 mm showed a population increase of the nematode, the average temperature of 25°C proved to be ideal for its development, demonstrating that Pratylenchus spp. has a favorable environment in the State of Mato Grosso for its population increase, due to the climatic conditions being propitious, having the producer to use management tactics for its control to minimize losses in its crops.